Molecular architecture and electrical properties in evaporated films of cobalt phthalocyanine - Alessio, P. [UNESP]; Oliveira, R. F. de [UNESP]; Aoki, P. H. B. [UNESP]; Pereira, J. D. A. S. [UNESP]; Braunger, M. L. [UNESP]; Furini, L. N. [UNESP]; Vieira, M. [UNESP]; Teixeira, S. R. [UNESP]; Job, Aldo Eloizo [UNESP]; Saenz, C. A. T. [UNESP]; Alves, Neri [UNESP]; Olivati, C. A. [UNESP]; et al. (Amer Scientific Publishers, 2012)
Thin films of cobalt phthalocyanine (CoPc) were deposited onto solid substrates through physical vapor deposition (PVD) by thermal evaporation up to 60 nm thick to determine their molecular architecture and electrical properties. The growth was monitored using UV-Vis absorption spectroscopy, revealing a linear increase for absorbance versus thickness. PVD films were found in the crystalline alpha phase and with the CoPc molecules forming ca. 45 degrees in relation to the substrate surface. The film surface was fairly homogeneous at the micro and nanoscales, with the roughness at ca. 3 nm. DC and AC electrical measurements were carried out for devices built with distinct structures. Perpendicular contact was established by depositing 60 nm CoPc PVD films between indium tin oxide (ITO) and Al, forming a sandwich-type structure (ITO/CoPc/Al). The current versus DC voltage curve indicated a Schottky diode behavior with a rectification factor of 4.2. The AC conductivity at low frequencies increased about 2 orders of magnitude (10(-9) to 10(-7) S/m) with increasing DC bias (0 to 5 V) and the dielectric constant at 1 kHz was 3.45. The parallel contact was obtained by depositing 120 nm CoPc PVD film onto interdigitated electrodes, forming an IDE-structured device. The latter presented a DC conductivity of 5.5 x 10(-19) S/m while the AC conductivity varied from 10(-9) to 10(-1) S/m between 1 Hz and 1 MHz, respectively, presenting no dependence on DC bias. As proof-of-principle, the IDE-structured device was applied as gas sensor for trifluoroacetic acid (TFA).
Keywords: Cobalt Phthalocyanine; Evaporated Film; Molecular Architecture; Electrical Property; Gas Sensor